2014
DOI: 10.1016/j.jallcom.2013.12.245
|View full text |Cite
|
Sign up to set email alerts
|

Glass-formation and corrosion properties of Fe–Cr–Mo–C–B glassy ribbons with low Cr content

Abstract: The effect of low amounts of Cr on glass forming ability and corrosion behavior of Fe (65-x) Cr x Mo 14 C 15 B 6 (x=0, 2, 4, 6, 8, 10 at.%) ribbons have been studied. It was found that the reduced glass transition temperature (T rg ) do not change significantly with Cr content. The glass forming ability (GFA) of this system is evaluated by the  m ,  and  parameters and the alloys containing 4 and 6 at.% were found to be the best glass formers in this system. The temperature interval of the supercooled liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…2a), it was observed a wide ΔTx window (41 • C), which can be associated with a higher stability of the amorphous phase and can also be promising for processing these alloys in this temperature range without losing the amorphous state [62,63]. Madinehei et al [64] showed that increasing Cr could positively affect GFA in traditional Fe-based amorphous alloys, enlarging the ΔTx window for a Fe-Cr-Mo-C-B system alloy. However, unlike the designed FeCrMoNbB PHE amorphous alloy, Cr amounts above 6% were found to have the opposite effect in those conventional Fe-based amorphous alloys.…”
Section: Crystallization Analysismentioning
confidence: 99%
“…2a), it was observed a wide ΔTx window (41 • C), which can be associated with a higher stability of the amorphous phase and can also be promising for processing these alloys in this temperature range without losing the amorphous state [62,63]. Madinehei et al [64] showed that increasing Cr could positively affect GFA in traditional Fe-based amorphous alloys, enlarging the ΔTx window for a Fe-Cr-Mo-C-B system alloy. However, unlike the designed FeCrMoNbB PHE amorphous alloy, Cr amounts above 6% were found to have the opposite effect in those conventional Fe-based amorphous alloys.…”
Section: Crystallization Analysismentioning
confidence: 99%
“…МС и упрочняющие покрытия, сформированные из МС на основе железа, имеют повышенную твердость [8], повышенную износостойкость [1,9,10], более низкие коэффициенты трения [11], жаростойкость [12,13], коррозионную стойкость [2,[14][15][16] и другие свойства [17,18] относительно материала основы.…”
Section: Introductionunclassified
“…Recently, Al-Y-Ni MGs have been prepared, exhibiting a tensile fracture strength of more than 1000 MPa combined with good bend ductility; the tensile strength is almost two times as high as that of conventional Al-based crystalline alloys [4,5]. Fe-Cr-Mo-C-B system MGs have been sprayed as protective coatings on numerous prototypes and parts, exhibiting better corrosion and wear resistance than conventional stainless steels and Ni-based alloys [6][7][8]. These performances of MGs have been proven to be of fundamental scientific interest with potential applications including drilling, shipbuilding industry and petroleum industry because of their contrast with conventional crystalline metals.…”
Section: Introductionmentioning
confidence: 99%